THE ARTISTIC CREATIVITY OF MARK CHEREMSHYNY AS A SOURCE OF REPRESENTING THE HISTORY OF FEMINITIVES OF THE UKRAINIAN LANGUAGE - Brus, Maria; Polyak , Iryna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Goal. The article characterizes the language creation of the Pokut writer Mark Cheremshina as a basis for studying the history of the Ukrainian language and the evolution of feminitives in particular. It is noted that the novelist’s creative activity reflected the peculiarities of the development of the Ukrainian literary language at that time and the specific features of his native Hutsul language and the entire Pokut region, where the ancient features of the Ukrainian language, especially in the vocabulary, were preserved in various manifestations. All the feminine vocabulary found in the artist’s works made it possible to testify and substantiate the concentration of many ancient phenomena and processes in dialect speech (lexical, word-forming, phonetic, grammatical), characteristic of the development of the feminine subsystem of the Ukrainian language. Research methodology. In the context of studying the evolution of the category of nouns with the meaning of a person of the female gender, it is fundamentally important to study the historical and scientific base. A living source that reflects the processes and ways of development of feminatives of the Ukrainian language is folk colloquial speech, concentrated not only in written, but also in oral creativity. The largest number of ancient specific features of the Ukrainian language was brought and preserved until now by colloquial speech, localized in Ukrainian dialects and dialects. And the presenter of such vernacular language is the work of writers originating from this or that region of Ukraine. Marko Cheremshina belongs to the artists of the artistic word, who in his work achieved a high level of embodiment of the features of the literary language of his time, the language of his own region and native language. Based on his prose, the common names of the female gender in synchronic and diachronic images were investigated. On the synchronic level, the lexical-semantic and structural-word-forming features of the category of feminitives, which were characteristic of the Ukrainian literary language at that time and entered the author’s lexicon, are considered, and on the diachronic level, it is shown which features of the historical development of feminitives are reflected in the language of the novelist. Methods of synthesis and analysis, descriptive and historical methods, methods of lexical, word-formation, and stylistic analysis were used to establish synchronic and diachronic phenomena. The theoretical basis for such a study was scientific research on the linguistic features of Mark Cheremshina’s work and the Hutsul language, and the source base was the two-volume edition of the works of this Ukrainian writer.